An investigation of anthropogenic pollution in soil samples from residential areas in Erzincan city center and its vicinity by evaluating chemical factors - Yalcin, Pasa; Kam, Erol; Yumun, Zeki Unal; Kurt, Dilek (SPRINGER HEIDELBERG, 2018)
To measure heavy metal pollution, 42 different soil samples were collected and analyzed from the center, cities, and villages of Erzincan. Average element concentrations in the soil samples in micrograms per gram were as follows: Cadmium (Cd, 6.1), Cobalt (Co, 52.2), Chromium(Cr, 739.6), Copper(Cu, 51.3), Nickel(Ni, 638.4), Lead (Pb, 14.2), and Zinc(Zn, 85.7), and these results were incompatible with natural background values. Heavy metal concentrations were at high levels, especially in agricultural regions and regions with mineral deposits. The results were compared to the allowable levels in soil dictated by pollution regulations in Turkey and some European countries. Krige (1962) method was used to evaluate the distribution of concentrations of heavy metals. Various methods such as Reverse Distance Weighted Interpolation Method (IDW), Local Polynomial, Radial-Based Function, and Kriging were used in preparing density maps. In the maps obtained, critical values for each heavy metal are defined. In addition, these critical values were compared with Krauskopf (1979) values. In this comparison, the values obtained in the samples showed ultramafic rocks in Erzincan region.
Keywords: Heavy metals; Pollution; Background; Soil samples; Erzincan; HEAVY-METAL POLLUTION; URBAN SOILS; AGRICULTURAL SOILS; FORAMINIFERA; TURKEY; SEA; Geology